Kualitas air sumur gali ditinjau dari parameter mikrobiologis di tepi sungai gajah wong yogyakarta - Amyati Amyati (JHeS (Journal of Health Studies), 2018)
This study aims to identify the bacteria Escherichia coli in the water dug wells owned by residents on the banks of the gajah wong river, Kotagede-Yogyakarta. Bacteria Eschericia coli is one cause of diarrhea that need to know its existence to prevention of diarrhea. This research used descriptive analytics.The results showed, all the well water as a positive contain Eschericia Coli. The closer the distance between the well and the river, the higher the content ofEschericia.Coli. 50% of dug well water sampled is still feasible for consumption because the content of Escherichia coli is still less than 50 MPN/100ml